Fire exit eaudiobook - Talty, Morgan (Recorded Books, Inc., 2024)
"Fire Exit, Morgan Talty's debut novel, is utterly consuming. The novel absolutely smolders. "Tommy Orange Does she remember this day? Does she remember it at all? Does she know this history this story her body holds secret from her? From the porch of his home, Charles Lamosway has watched the life he might have had unfold across the river on Maine's Penobscot Reservation. On the far bank, he caught brief moments of Roger and Mary raising their only child, Elizabeth from the day she came home from the hospital to her early twenties. But there's always been something deeper and more dangerous than the river that divides him from this family and the rest of the tribal community. It's the secret that Elizabeth is his daughter, a secret Charles is no longer willing to keep. Now it's been weeks since he's seen Elizabeth and Charles is worried. As he attempts to hold on and care for what he can: his home and property, his alcoholic, quick-tempered and big-hearted friend Bobby, and his mother, Louise, who is slipping ever-deeper into dementia he becomes increasingly haunted by his past. Forced to confront a lost childhood on the reservation, a love affair cut short, and the death of his beloved stepfather, Fredrick, in a hunting accident death that he and Louise cannot agree where to lay the blame Charles contends with questions he's long been afraid to ask. Is it his secret to share? And would his daughter want to know the truth? From award-winning author of Night of the Living Rez, Morgan Talty's debut novel, Fire Exit, is a masterful and unforgettable story of family, legacy, bloodlines, culture and inheritance, and what, if anything, we owe one another.